Cross-Selling Sharia Gold Savings: A Hedging Strategy for Hajj Financial Risk Mitigation - Iska Nur Mawarda Mawarda; Lely Ana Ferawati Ekaningsih; Wiwit Mustafidah (STAI AN-NAJAH INDONESIA MANDIRI, 2025)
This research analyzes the cross-selling strategy of gold savings to strengthen the financing guarantee for Hajj Pilgrimage Organizing Fees (BPIH) for customers at Bank Syariah Indonesia KCP Banyuwangi Rogojampi. Utilizing a qualitative Case Study approach involving interviews, observation, document analysis, and SWOT analysis, the findings reveal that the main strengths lie in the bank's reputation, the transparency of the murabahah contract, and support from the BYOND digital platform. Weaknesses include limitations in employee training/human resources and the absence of standardized educational SOPs. Opportunities arise from payroll customer segments and digitalization trends, while threats encompass market competition and gold price volatility. The analysis results in the formulation of SO (digital enhancement and collaboration), WO (training and SOP development), ST (reputation-based education), and WT (sharia financial literacy campaign) strategies. It is concluded that the cross-selling strategy for gold savings is effective as a hedging instrument against BPIH increases, with recommendations to strengthen education, human resources, and service digitalization.